Simulasi drag-type turbine ditinjau dari pengaruh variasi sudut kelengkungan sudu untuk diaplikasikan dalam pipa air - Muh. Alwan Rosyidi; Syamsul Hadi; Dominicus Danar Dono Dwi Prija Tjahyana (Badan Kerja Sama Teknik Mesin Indonesia, 2017)
The high rainfall and the high-rise building in urban areas are important potential factor in developing the alternative energy. A concept of Horizontal Axis Water Turbine is proposed as a media to generate the electrical energy with low head condition. This research focuses on the effect of various blade curvature angle on Drag-type Turbine with simulation method. The purpose of this research is to find the maximum performance from a various blade curvature angle of 100°, 110°, 120°, 130°, 140°, and 150°. The result is the maximum performance obtain at blade curvature angle 150° with torque value 16,8 Joule.